Effect of soy protein a humidifier in the qualitative characteristics of the Barker factory of beef and chicken meat elderly - Baghdad Science Journal (مجلة بغداد للعلوم)
The purpose of this study was to know the effect of adding different percentages of soy protein a humidifier to mix Sarcoma Barker component of the beef mixture Alkhalt added Alber elderly chicken with five ratios were manufacturing Alberkr discs for sensory evaluation